1994
DOI: 10.1210/en.134.5.2011
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of glucagon-like peptide-1 secretion by muscarinic agonist in a murine intestinal endocrine cell line

Abstract: Studies on the cholinergic regulation of intestinal L-cells have been focused on the release of enteroglucagon, but the signal transduction pathways were not defined. These were here investigated by using as index the release of immunoreactive glucagon-like peptide-1 (GLP-1) from the endocrine cell line STC-1, that has been shown to contain proglucagon mRNA transcripts. Abundant GLP-1 immunoreactivity was revealed in STC-1 cells at immunocytochemistry and by RIA. The cell content was 4927 +/- 689 pg/10(6) cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 0 publications
1
46
0
Order By: Relevance
“…Probably this occurs in addition to indirect means of stimulation, e.g. by the release of gastric inhibitory peptide (GIP) from endocrine cells located in the proximal small intestine (Herrmann-Rinke et al 1996;Damholt et al 1999) or through the activation of muscarinic receptors that are located on the intestinal L-cells (Abello et al 1994;Balks et al 1997). The indirect mechanism is supposed to predominate in the ileum under normal conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Probably this occurs in addition to indirect means of stimulation, e.g. by the release of gastric inhibitory peptide (GIP) from endocrine cells located in the proximal small intestine (Herrmann-Rinke et al 1996;Damholt et al 1999) or through the activation of muscarinic receptors that are located on the intestinal L-cells (Abello et al 1994;Balks et al 1997). The indirect mechanism is supposed to predominate in the ileum under normal conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The stimulus for the early postprandial release of GLP-1 secretion is not clearly understood. Studies in animals have indicated a possible role for GIP and\or the parasympathetic system in release of GLP-1 from the ileum in response to the presence of food in the duodenum and jejunum [27,28], but no such mechanism has been demonstrated in man [1]. We suggest that the fall in plasma NEFA levels after ingestion of food may be an important mechanism by which GLP-1 release is either stimulated or enhanced and that failure of NEFA suppression may be partly responsible for the impaired GLP-1 secretion seen in obesity.…”
Section: Discussionmentioning
confidence: 99%
“…The GLP-1 assay was performed as described elsewhere [1]. Briefly, an antiserum against GLP-1(7-36) amide was raised in a rabbit by immunization with synthetic GLP-1(7-36) amide conjugated to bovine serum albumin (BSA).…”
Section: Glp-1mentioning
confidence: 99%